PENGEMBANGAN MEDIA PEMBELAJARAN ANIMASI DENGAN MACROMEDIA FLASH 8 PADA MATERI JENIS-JENIS KOLOID - Novia Sari; Elvi Yenti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The lack of various learning media used in the learning process constituted the background of this research. This research aimed at developing a product in the form of animation learning media, determining validity and practicality levels of animation learning media with Macromedia Flash 8 on Colloid Types lesson. It was Research and Development (R&D) with ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. This research was administered to the twelfth-grade students of MIPA 3 at State Senior High School 3 Pekanbaru. The validation result by media and material experts showed that its percentage was 98.57% with very valid category. The percentage of teacher practicality test was 98.09% with very practical category, and the percentage of student response practicality test was 84.40% with very practical category.Keywords : Learning Media, Animation, Macromedia Flash, Colloid.